2011
DOI: 10.1111/j.1553-2712.2010.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physicians’ Knowledge and Provision of Child Passenger Safety Information

Abstract: Objectives: While physicians provide discharge instructions to patients and families following emergency department (ED) visits, injury prevention information may not be routinely included in these instructions. This study assessed emergency physicians' knowledge and provision of child passenger safety (CPS) information to patients following motor vehicle crashes (MVCs).Methods: This study was both a survey of emergency physician knowledge and provision of CPS information and an examination of frequency of CPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Training resources which are accessible by all HCPs include CPS courses offered by the AAP. Continuing education related to CPS is important for HCPs to maintain current knowledge levels and stay current on recommendations about CPS (Zonfrillo et al, 2011). Future research in this area should focus on frequency and efficacy of current training provided to HCPs related to CPS issues.…”
Section: Discussionmentioning
confidence: 96%
“…Training resources which are accessible by all HCPs include CPS courses offered by the AAP. Continuing education related to CPS is important for HCPs to maintain current knowledge levels and stay current on recommendations about CPS (Zonfrillo et al, 2011). Future research in this area should focus on frequency and efficacy of current training provided to HCPs related to CPS issues.…”
Section: Discussionmentioning
confidence: 96%
“…Although low, respondents to this survey indicated greater provision of car seat information in ED discharge instructions than reported in a prior survey of pediatric ED chairs and division chiefs, where less than one third reported providing discharge instructions containing pediatricspecific child passenger safety topics. 18 Even though there are currently no requirements for the distribution of child passenger safety information from the ED, it would be reasonable to expect all families discharged following an MVC would receive accurate information regarding when to replace child safety seats and restraint use recommendations that are consistent with the current national guidelines for child passenger safety. 29Y31 Further gains in the number of parents who receive child passenger safety information at ED discharge may be realized through the implementation of electronic medical record systems that allow for standardized, computerized discharge instructions.…”
Section: Discussionmentioning
confidence: 98%
“…13Y16 Currently, ED visits represent an underutilized opportunity to provide parents with recommendations for optimal child passenger safety. 17,18 The ED also could link parents to community child passenger safety resources at a time of potentially heightened awareness of the importance of child passenger restraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 30% of ED chiefs reported their EDs routinely gave child passenger safety instructions to pediatric motor vehicle collision (MVC) patients and only 8.6% of pediatric MVC charts had documented safety discharge instructions. 24 Macy et al found that while 95% of pediatric emergency physicians and 82% of adult emergency physicians felt that it was their role to educate parents on child safety practices, less than half gave proper injury prevention advice in hypothetical clinical scenarios. 25 Even when a department is involved in some injury prevention activities, many ED physicians and staff feel this is not enough.…”
Section: Discussionmentioning
confidence: 99%